Natural resources heterogeneity and environmental sustainability in G20 nations: post-COP28 analysis - Alomair, Abdulrahman; Ibrahim, Ridwan Lanre; Al Naim, Abdulaziz S. (Frontiers in Environmental Science, 2025)
This study presents the maiden empirical evidence disintegrating the impacts of natural resources on environmental sustainability into production and consumption models. For easy trackability of the empirical evidence, environmental sustainability is captured by carbon emissions and ecological footprint in selected G20 economies with ta running from 1995 to 2019. To elaborate the study’s contributions, green policies comprising green energy, green technology, and green finance together with environmental tax, financial development, economic growth, and population are considered as covariates in STIRPAT embedded theoretical framework. The empirical verification anchors on second-generation estimators entailing cross-sectional autoregressive distributed lag (CS-ARDL), common correlated effects mean group autoregressive mean group (AMG), and method of moment quantile regression The fallouts from the analyses reveal that the production and consumption of natural resources based on coal and oil hinder environmental sustainability, although the former has greater effects than the latter. Interestingly, natural gas provides diverging direct and indirect impacts on both pollutants. More so, green policies and environmental taxes support promoting environmental sustainability. Additionally, two channels of causalities, including unidirectional and bidirectional nexuses, are apparent from the estimated model. The study highlights the importance of eliminating fossil fuel subsidies and making substantial investments in green policies as key recommendations for policy action.